Jurnal Akuntansi & Investasi: Analisis Praktik Corporate Social Responsibility Perusahaan Furniture di Kabupaten Jepara - Aida Nahar (Akuntansi FE UMY, 2012)
Corporate social responsibility (CSR) is a transparent business practices, which are based on ethical values, with particular attention to employees, communities and the environment, and designed to meet the wishes of the shareholders and the public in general. Effort to understand and analyze the practice of CSR in a company is interesting, considering the practice of CSR is not a uniform practice and its implementation is highly dependent on the unique characteristics inherent in the company.